CHANGE IN EMOTIONAL EXPERIENCES OF SENIOR SCHOOL LEARNERS: LONGITUDINAL STUDY - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2011)
The article approaches the problem of spiritual value education in the context of challenges imposed by globalisation. Following the opinions of theologians, philosophers and educational researchers, the essential contours of spirituality expression are actualised. In the context of such ideas the role of emotional experiences, as a relevant dimension of spirituality, in internalisation of values is substantiated. Following B. Dodonov’s conception, it is stated that the influence of emotions on internalisation of values depends on the need of specific emotions felt by an individual, which manifests itself through a particular attraction towards these emotions as positive values. The formed favourable attitude is an expression of this need, which reflects individual’s emotional orientation and his/her relation with spiritual values.The article presents the data of the longitudinal study (1998–2009), which show that during the period of 10–11 years the most considerable positive changes were observed in upper secondary learners’ evaluations of communicative and altruistic emotions (an increase of one fifth in the number of respondents, who evaluated these emotions as the most pleasant was observed) and slightly more positive changes were identified in evaluation of praxical, gnostic and esthetical values. The opinion that an increasing attraction of school learners towards these emotions that make up the core of spiritual experiences results in strengthening of their links with spiritual values (moral, gnostic and esthetical) is followed. An increasing favour towards hedonistic emotions and partially to gloristic, pugnistic and acquisitive values is seen as considerably negative phenomenon. Changes in perceiving of these emotions, as well as previously identified changes in understanding meanings of values, allow stating that next to identified positive changes, the orientations towards values that may be considered as a certain source of pragmatism, hedonism and utilitarianism are observed among senior school learners. The dependence of emotion changes on learners’ gender and type of school is not considerable.
Keywords: globalisation; spirituality; emotions; senior school learners; change